Implementation of the Discovery Learning Model to Improve Students' Social Studies Achievement at SMP Negeri 3 Lembah Seulawah - Angkat, Mene; Nurimah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to investigate the application of the Discovery Learning model to improve the social studies learning achievement of seventh-grade students at SMP Negeri 3 Lembah Seulawah. The background of this research lies in the observation that students often experience difficulties in understanding abstract concepts in social studies, which in turn affects their overall achievement. Discovery Learning, as an active and student-centered approach, emphasizes the process of exploration, hypothesis testing, and knowledge construction, enabling students to develop critical and analytical thinking skills. The research employed a classroom action research design carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. Data were collected using tests, observations, and documentation, and then analyzed descriptively and quantitatively. The findings reveal a significant improvement in students’ learning achievement after the implementation of Discovery Learning, as indicated by the increase in average test scores and the percentage of students meeting the minimum mastery criteria. Moreover, students demonstrated higher levels of engagement, motivation, and independence during the learning process. This study concludes that the Discovery Learning model is effective in enhancing both cognitive and affective aspects of students’ social studies learning achievement, and it is recommended for broader classroom application.